Wi-Fi Enabled Remote Control Surveillance Vehicle: Design, Implementation, and Performance Analysis - Junita Junita; Nicholas Kevin Setiadi (Telkom University, 2025)
The rapid advancement of wireless technology has expanded the possibilities for remote-controlled systems, particularly in surveillance and safety applications. This study aims to develop a 4G-enabled remote surveillance vehicle using a Raspberry Pi 4 Model B microprocessor to achieve long-range control and real-time visual feedback. The vehicle integrates a Raspberry Pi 4 with two Electronic Speed Controllers (ESCs) connected to three gearbox motors for movement, along with an OV5647 camera module mounted on a 2-axis gimbal controlled by MG90S servos. The system is programmed in JavaScript using Node.js and Visual Studio Code, enabling a webserver for bidirectional communication between the vehicle and the controller. Key tests demonstrated a maximum operational range of 1.11 km, with the potential for further distance as connectivity permits. The vehicle exhibited an average battery life of 46 minutes and a latency of approximately 49 ms under stable 4G conditions. Additionally, it successfully traversed diverse terrains, including gravel and sand. The findings highlight the vehicle's capability for remote surveillance in hazardous or inaccessible environments, reducing human risk. Future enhancements could include integrating additional sensors for broader applications. This research underscores the feasibility of using cost-effective, off-the-shelf components to build a robust, long-range surveillance system